2022
DOI: 10.1038/s41467-022-32376-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS CoV-2 mRNA vaccination exposes latent HIV to Nef-specific CD8+ T-cells

Abstract: Efforts to cure HIV have focused on reactivating latent proviruses to enable elimination by CD8+ cytotoxic T-cells. Clinical studies of latency reversing agents (LRA) in antiretroviral therapy (ART)-treated individuals have shown increases in HIV transcription, but without reductions in virologic measures, or evidence that HIV-specific CD8+ T-cells were productively engaged. Here, we show that the SARS-CoV-2 mRNA vaccine BNT162b2 activates the RIG-I/TLR – TNF – NFκb axis, resulting in transcription of HIV prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 71 publications
6
19
2
Order By: Relevance
“…Our cohort-based analysis also found no evidence that COVID-19 mRNA vaccination induced changes in HIV reservoir size, nor in total, 5'-defective, or 3'-defective proviral loads. This is consistent with findings from of three studies that assessed smaller numbers of participants for this outcome using similar approaches [27,29,31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our cohort-based analysis also found no evidence that COVID-19 mRNA vaccination induced changes in HIV reservoir size, nor in total, 5'-defective, or 3'-defective proviral loads. This is consistent with findings from of three studies that assessed smaller numbers of participants for this outcome using similar approaches [27,29,31].…”
Section: Discussionsupporting
confidence: 91%
“…Taken together with similar findings from other studies [27][28][29]31], we conclude that there is now a strong body of evidence indicating COVID-19 immunization is safe and effective in PWH [4][5][6][7][8][9][10][11][12]. This should provide additional reassurance to PWH and their care providers regarding the safety of COVID-19 mRNA vaccines.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this context, the increased HIV transcription is accompanied by enhanced HIV-specific CD8 + T-cell responses, pointing to standard vaccines as a potential tool to reverse HIV latency to enable eradication by cytotoxic T-cells [ 93 ]. Accordingly, a recent study showed that BNT162b2 vaccine activates the RIG-I/TLR–TNF–NFkB axis, resulting in transcription of HIV proviruses; in parallel, Nef-specific CD8 + T-cells increase and acquire cytotoxic effector functions, which correlate with reduction of cell-associated HIV-mRNA, suggesting killing or suppression of cells transcribing HIV; however, significant depletion of intact proviruses was not observed, highlighting challenges to achieving HIV reservoir reductions [ 94 •]. Nevertheless, the interplay between vaccines, immune system, and latent HIV infection is yet to be thoroughly understood and deserves further research in order to inform future HIV eradication strategies.…”
Section: Sars-cov-2 Vaccine Efficacy and Safety In Plwhmentioning
confidence: 99%
“…However, it has recently been reported that following SARS-CoV-2 mRNA vaccination, a transient HIV expression occurs, manifesting primarily as the activation of HIV-Nef-specific CD8+ T-cell responses. Even though researchers have not observed a significant depletion of intact proviruses, this CD8+ T-cell induction is correlated with significant decreases in cell-associated HIV mRNA, suggesting the killing or suppression of cells transcribing HIV [ 155 ]. Some mRNA vaccines targeting HIV antigens are under development for both prophylactic and therapeutic settings.…”
Section: Lessons Learned and Future Directionsmentioning
confidence: 99%